EFEKTIVITAS PENEGAKAN DISIPLIN PEGAWAI NEGERI SIPIL DI INDONESIA - April Rio; Fakhris Lutfianto Hapsoro (Qiyas : Jurnal Hukum Islam dan Peradilan, 2022)
Abstract : Civil Servants are the first element as human resources that play a role in government development. The aim of the Government to issue Regulations on Civil Servant Discipline is to guarantee the order and smooth running of the duties of the Civil Servants themselves, so that in carrying out their main duties and functions as government apparatus they can run properly which in the end can support development in Indonesia. But in reality, regulations issued by the government cannot suppress disciplinary violations committed by civil servants. There are still many civil servants who are undisciplined in their work, lack awareness to complete tasks, and lack a sense of responsibility for their work. This is because there is no concern for the implementation of its duties, principals and functions, so that it indirectly causes the activities of the agency to not go well. The formulation of the problem in this study is how is the application of civil servant discipline in DKI Jakarta? This research uses juridical-empirical research and legal sociology approaches to determine the effectiveness of civil servant disciplinary regulations. It is known that there are already regulations governing civil servant discipline, namely PP No. 94 of 2021 concerning PNS Discipline, but in sociological law enforcement there are still obstacles in upholding civil servant discipline. So it is necessary to have a solution in order to increase the discipline of Civil Servants to reduce the number of violations committed.